2013
DOI: 10.1371/journal.pone.0076080
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, Temporal, and Habitat-Related Variation in Abundance of Pelagic Fishes in the Gulf of Mexico: Potential Implications of the Deepwater Horizon Oil Spill

Abstract: Time-series data collected over a four-year period were used to characterize patterns of abundance for pelagic fishes in the northern Gulf of Mexico (GoM) before (2007–2009) and after (2010) the Deepwater Horizon oil spill. Four numerically dominant pelagic species (blackfin tuna, blue marlin, dolphinfish, and sailfish) were included in our assessment, and larval density of each species was lower in 2010 than any of the three years prior to the oil spill, although larval abundance in 2010 was often statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 45 publications
1
82
0
Order By: Relevance
“…The northern Gulf is considered to be important early life habitat of billfishes, tunas and swordfish. The mean densities of C. hippurus (ranging from 0.40 to 1.60 larvae 1000 m −3 ) were lower than that of blackfin tuna but comparable to sailfish and blue marlin (Simms et al ., ; Rooker et al ., , ), whereas densities of C. equiselis (ranging from 0.02 to 0.20 larvae 1000 m −3 ) were comparable with swordfish and white marlin in the same region (Rooker et al ., ).…”
Section: Discussionmentioning
confidence: 94%
“…The northern Gulf is considered to be important early life habitat of billfishes, tunas and swordfish. The mean densities of C. hippurus (ranging from 0.40 to 1.60 larvae 1000 m −3 ) were lower than that of blackfin tuna but comparable to sailfish and blue marlin (Simms et al ., ; Rooker et al ., , ), whereas densities of C. equiselis (ranging from 0.02 to 0.20 larvae 1000 m −3 ) were comparable with swordfish and white marlin in the same region (Rooker et al ., ).…”
Section: Discussionmentioning
confidence: 94%
“…If tags had not remained attached on fish through late winter, we would not have identified fish that traveled to the South American coast before returning to the Gulf of Mexico. Given the diversity in sailfish movement patterns observed across sampling years, it is inadequate to rely upon a small number of tracks to monitor potential shifts in billfish habitat following a major environmental disaster, such as the Deep Horizon oil spill53. Since billfishes likely spawn at multiple sites throughout the Atlantic315455, the loss of a particular spawning site may have limited impacts on the populations.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae have been collected in areas with SSTs between ~24 and 28°C, sea surface salinity between ~35.5 and 37.0 and temperature at 200 m depth between ~15 and 22°C (Muhling et al ., ). Previous studies demonstrated that, among different environmental parameters, SST is the most important parameter defining areas where spawning may be observed (Muhling et al ., ) for bluefin tuna and other tunas (Rooker et al ., ). In fact, the probability of bluefin tuna larvae occurrence derived from in situ surveys shows a consistent relationship with SST (Fig.…”
Section: Introductionmentioning
confidence: 97%